The Impact of a Plant-Based Diet on Inflammatory Symptoms In Rheumatoid Arthritis: A Review - Moszkowicz, Justyna; Ufniarski, Tomasz; Piech, Aleksandra; Grodzińska, Martyna; Kleczkowska, Maria; Poplicha, Karol; Sobkiewicz, Piotr; Pasierb, Karolina; Kardasz, Patrycja; Siuzdak, Bartłomiej; Jutrzenka, Marta (Quality in Sport, 2025)
Introduction: This review evaluates the impact of plant-based diets on the inflammatory symptoms in patients with rheumatoid arthritis (RA). RA is a chronic autoimmune inflammatory disease affecting approximately 1% of the global population and significantly impairing quality of life. Although pharmacological treatment with disease-modifying antirheumatic drugs (DMARDs) remains the cornerstone of therapy, but non-pharmacological interventions, including dietary changes, are also being recognised as important. Plant-based diets that are rich in fibre, antioxidants, and unsaturated fatty acids, have demonstrated anti-inflammatory properties that may modulate disease activity and improve clinical outcomes in RA patients. A systematic analysis of clinical trials and observational studies reveals that vegan, vegetarian, and plant-forward dietary patterns contribute to significant reductions in disease activity scores (DAS28), inflammatory markers such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), and subjective pain and physical function assessments with vegan, vegetarian, and plant-forward dietary patterns. Proposed mechanisms include decreased pro-inflammatory cytokines, improved gut microbiota diversity, weight reduction, and modulation of immune pathways such as autophagy. While the results are promising, further large-scale randomised controlled trials are necessary to clarify the optimal dietary approaches and their long-term benefits in RA management. Objective: This review aims to assess the impact of plant-based diets on inflammatory symptoms in patients with rheumatoid arthritis (RA). Materials and Methods: A review of the available literature from the PubMed, Scopus, and Web of Science databases published within the last 20 years.